PENYELESAIAN KREDIT MACET MELALUI FORUM NON LITIGASI PADA PROSES KEPEMILIKAN RUMAH DI PT BANK TABUNGAN NEGARA CABANG PEKANBARU - Deddy Suryadi Akhyar; Ali Ismail Shaleh (Faculty of Law - Tarumanagara University, 2021)
Houses are a primary need for some families, both those living in rural areas and in urban areas, which is a primary need. The fulfillment of these primary needs cannot be met by everyone to buy in cash. Therefore, a financial institution is needed to provide financial assistance in the form of credit distribution, especially in housing loans (KPR).This research examines two problems, namely the obstacles in solving bad credit at PT Bank Tabungan Negara Pekanbaru Branch and how to solve bad credit through non-litigation forums on the home ownership process carried out by PT BanK Tabungan Negara Pekanbaru Branch. This research uses observational research, which is a field research that is attempted to provide a descriptive description of the reality that occurs in society, where the author in conducting observational research uses qualitative methods. Broadly speaking, the factors that can hinder the occurrence of non-performing loans can be classified into internal and external factors, where the non-litigation settlement of bad loans at PT Bank Tabungan Negara Pekanbaru Branch takes several steps recommended by creditors, namely pre-negotiation, negotiation implementation. , post negotiation. From the research results, it can be concluded that the obstacles in settlement through non-litigation are incomplete documents / debtor credit data, and can take the form of difficulties in collecting debts because the debtor has a poor character. Bad faith from the debtor, lack of awareness of the debtor in completing his loan facility, timeliness because the debtor's improperly repaying his debt results in a protracted settlement, so that the burden borne by the debtor is getting bigger, non-litigation settlement is Rescheduling, Restructuring, and Reconditioning, the factor that causes PT Bank Tabungan Negara Pekanbaru Branch to choose to settle non-performing loans through non-litigation channels is time, the results achieved if through non-litigation channels the settlement of bad credit in home ownership loans (KPR) can get maximum results, good faith reason The non-litigation route was chosen, because there is still a willingness from the debtor to settle the credit.